2018
DOI: 10.3390/ijms19041011
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Genetic Effects of CMIP Polymorphisms on the Risk of Type 2 Diabetes and Obesity: A Family-Based Study in China

Abstract: C-Maf Inducing Protein (CMIP) gene polymorphisms were reported to be associated with type 2 diabetes mellitus (T2DM). Whether the association between CMIP and T2DM is mediated via obesity-related phenotypes is still unclear. We analyzed the association of CMIP rs2925979 with T2DM and a comprehensive set of obesity-related phenotypes in 1576 families ascertained from a Chinese population. These families included a total of 3444 siblings (1582 with T2DM, 963 with prediabetes, and 899 with a normal glucose level)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, this study also found for the first time a significant association between CMIP rs16955379 and GDM. Previous studies suggested that CMIP was associated with lipid metabolism, and its rs16955379 variant was linked to lipid metabolism disorders [ 25 ], which might thus increase the risk of T2DM [ 26 ]. Cho et al [ 11 ] found C alleles in rs16955379 was a risk factor for T2DM in East Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study also found for the first time a significant association between CMIP rs16955379 and GDM. Previous studies suggested that CMIP was associated with lipid metabolism, and its rs16955379 variant was linked to lipid metabolism disorders [ 25 ], which might thus increase the risk of T2DM [ 26 ]. Cho et al [ 11 ] found C alleles in rs16955379 was a risk factor for T2DM in East Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the association between the CMIP gene and diseases such as mental neuropsychiatric disorder ( Eicher & Gruen, 2015 ; Luo et al, 2017 ; Wang et al, 2015 ), cancer ( Juan et al, 2019 ), and metabolic disease ( Cao, Wang & Wu, 2018 ; Mo et al, 2018 ). In this study, we included 1,536 participants to study the association between four tag SNPs (rs12925980, rs22287112, rs3751859 and rs77700579) of the CMIP gene and SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a potential function of CMIP in other organs and tissues can be inferred by the association of genetic variants with a number of pathologies. Accordingly, polymorphisms in CMIP sequence have been linked to the susceptibility to developing type 2 diabetes [ 22 , 23 , 24 , 25 ], to a decreased homeostasis model assessment of β-cell function and increased fasting plasma glucose [ 26 , 27 ], to adiponectin levels [ 28 , 29 ], to language impairment and autism [ 30 , 31 , 32 , 33 ], to adenylate cyclase 3 deficiency in the olfactory epithelium [ 34 ], to dyslipidemia associated with IgA nephropathy [ 35 , 36 ], to blood lipoprotein content [ 37 ], and adipocyte lipolysis [ 38 ]. Moreover, partial deletions have been described in some patients suffering from autism and gastro-intestinal disorders [ 39 ].…”
Section: C-maf Inducing Protein: Structural and Functional Aspectsmentioning
confidence: 99%